Major heavy metals and human gut microbiota composition: a systematic review with nutritional approach - Mahsa Rezazadegan; Bita Forootani; Yeganeh Hoveyda; Niloufar Rezazadegan; Reza Amani (Journal of Health, Population and Nutrition)
Abstract Background The human gut microbiota has a critical role in several aspects of host homeostasis, such as immune development, metabolism, nutrition, and defense against pathogens during life. It can be sensitive to xenobiotics including drugs, diet, or even environmental pollutants, especially heavy metals (HMs). The findings of some previous studies are heterogeneous due to the inclusion of various types of study (human, and animal studies) and wide exposures (phthalate, bisphenol A, HMS, etc.), and no comprehensive systematic review has investigated the association between HMs exposure and human gut microbiota composition. Therefore, we carried out a systematic review of human observational studies to examine this association. Main body of the abstract PubMed, Scopus, ISI Web of Science, and Google Scholar were searched using Medical Subject Headings (MeSH) and non-MeSH terms. Eventually, 12 studies for arsenic (As), lead (Pb), mercury (Hg), and cadmium (Cd) were included in this study. No eligible study was found for Aluminium. Short conclusion The findings showed exposure to HMs disturbs the composition of gut microbiota and can lead to dysbiosis. Exposure to high levels of As, Pb, and Hg increased the abundance of Collinsella as pathobionts. Evidently, it is related to leaky gut, oxidative stress, and several diseases such as inflammatory bowel disease and cancers. Probiotic treatment and nutritional strategies such as high fiber intake and following antioxidant-rich diets should be considered in terms of HMs exposure.